Pengaruh Kepemimpinan, Pengembangan Karir dan Motivasi Kerja Terhadap Kepuasaan Kerja - Agussupriadi, Raja; Ali, Hapzi (Journal of Accounting and Finance Management, 2024)
The influence of leadership, career development, and work motivation on job satisfaction is a scientific article of literature study in the scope of human resource management. The purpose of this article is to build a hypothesis of the influence between variables that will be used in subsequent research. The research object is in online libraries, Google Scholar, Mendeley, and other academic online media. The research method with library research is sourced from e-books and open access e-journals. Qualitative descriptive analysis. The results of this article: 1. Leadership influences Job Satisfaction; 2. Career Development influences Job Satisfaction; and 3. Work Motivation influences Job Satisfaction.